2020
DOI: 10.22441/jiess.2020.v1i1.005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Good Corporate Governance on Sukuk Rating

Abstract: This objective of this study to determine the influence of sukuk ratings on corporate governance. Proxy of the corporate governance that used is institutional ownership, frequency of board meeting, board size, and audit committee. The population in this studies are financial and non-financial companies listed on the Indonesia Stock Exchange (IDX), and issue bonds that are rated by PEFINDO in 2012-2017. The research was conducted with quantitative methods. The analysis methods used in this study is multiple lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Additionally, the imprecise relationship between FDQ and earnings management is shown by Hassan and Marston (2019), who assert that if the FDQ is low, the tendency to make earnings management adjustments is higher. In addition, the relationship between the ABR variable and earnings management is indistinct, as found in research by (Yuwono and Aurelia 2021), Astuti (2020), Ningrum et al (2019), and Ulfa (2019). They concluded that financial leverage as an indicator of ABRs had an effect on earnings management.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, the imprecise relationship between FDQ and earnings management is shown by Hassan and Marston (2019), who assert that if the FDQ is low, the tendency to make earnings management adjustments is higher. In addition, the relationship between the ABR variable and earnings management is indistinct, as found in research by (Yuwono and Aurelia 2021), Astuti (2020), Ningrum et al (2019), and Ulfa (2019). They concluded that financial leverage as an indicator of ABRs had an effect on earnings management.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, there are two types of Sukuk issued in Indonesia, namely those issued by the government called state Sukuk or SBSN (State Sharia Bonds) and those issued by companies called corporate Sukuk. According to Astuti (2020), a study on GCG, which consisted of default risk, accountability, disclosure, and transparency, is considered crucial (Pranoto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Astuti (2020), Revenue Sharing Fund is a fund sourced from the State Budget Revenues that are allocated to regions with a certain percentage rate, to fund regional needs in the context of implementing decentralization. Revenue Sharing Fund includes tax results and natural resource results.…”
Section: Revenue Sharing Fundmentioning
confidence: 99%